2013
DOI: 10.1074/jbc.m113.454140
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lipocalin-2-Chemokine Axis in the Development of Neuropathic Pain following Peripheral Nerve Injury

Abstract: Background:In the central nervous system, the role of LCN2 as a chemokine inducer has been previously reported. Results: Peripheral nerve injury increased LCN2 expression. Lcn2 deficiency attenuated pain hypersensitivity, microglial activation, and chemokine production. Chemokine expression and pain behavior were induced by LCN2. Conclusion: The LCN2-chemokine axis plays a critical role in the pathogenesis of neuropathic pain. Significance: LCN2 can be targeted for treatment of neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 66 publications
1
49
0
Order By: Relevance
“…Because we issued our first report on the glial expression of LCN2 (41, 55), several studies have demonstrated the potentially important roles played by LCN2 in the physiology and pathology of the CNS (38,44,47,56). Nevertheless, its functional roles in neuroinflammation and related diseases of the CNS are far from clear, and the results of some previous studies have been contradictory.…”
Section: Discussionmentioning
confidence: 83%
“…Because we issued our first report on the glial expression of LCN2 (41, 55), several studies have demonstrated the potentially important roles played by LCN2 in the physiology and pathology of the CNS (38,44,47,56). Nevertheless, its functional roles in neuroinflammation and related diseases of the CNS are far from clear, and the results of some previous studies have been contradictory.…”
Section: Discussionmentioning
confidence: 83%
“…LCN2 knockout (KO) mice were provided by Dr. Shizou Akira (Osaka University, Japan). The breeding and genotyping of LCN2 KO mice were performed as described previously [32]. All animal procedures were approved by the Committee on the Ethics of Animal Experiments of the Kyungpook National University.…”
Section: Reagents and Micementioning
confidence: 99%
“…Recombinant mouse LCN2 protein was prepared as described previously [32,33]. Briefly, recombinant LCN2 protein was expressed as a glutathione S-transferase (GST) fusion protein in BL21 strain E. coli, which does not synthesize siderophore.…”
Section: Reagents and Micementioning
confidence: 99%
“…In rat brain, LCN2 mRNA and protein were upregulated after neuronal injury induced by kainite (Chia et al 2011) or after neuroinflammation induced by systemic LPS injections (Ip et al 2011). Some papers showed that astrocytes produced LCN2 (Bi et al 2013), but other papers showed that LCN2 colocalized with neurons, not astrocytes or microglia (Jeon et al 2013; Mucha et al 2011; Skrzypiec et al 2013). Our data suggest that ischemic neurons (not glia) produced LCN2 in rat and human stroke brains (Xing et al 2014).…”
Section: Neuronal Help-me Signals and Neuron-immune Interactionsmentioning
confidence: 99%